Assessment of solar shading performance of courtyard houses in desert climate of Kashan, Iran. (1st November 2020) - Teshnehdel, Saeid; Soflaei, Farzaneh; Shokouhian, Mehdi
ABSTRACT: This paper concentrates on the effect of courtyard parameters on the shading function of courtyard houses in hot desert climates; BWh based on Köppen climate classification. The ultimate goal is to optimize the designing pattern for a courtyard regarding orientation, dimensions, and proportions, to enhance the shading performance and improve outdoor thermal comfort. For this purpose, 10 historical courtyard houses were selected with geometrical properties and different orientations from the hot desert climate of Kashan in Iran. The three-dimensional numerical model was applied, by Design Builder, to simulate sunlit and shaded areas. A field measurement was conducted on the shading performance of Borujerdi courtyard house in Kashan. A validation study was performed on the numerical model using the physical data and a close agreement was achieved. The shading index that was previously suggested by authors was employed based on hourly average temperature to investigate the correlations between the index and courtyard's orientation and geometrical properties. Results illustrate that the courtyard's design alternatives, particularly length-to-width ratio and height, have influential impacts on shading performance. Finally, some design recommendations for courtyard houses in hot desert regions were extracted to enhance the shading performance and increase the thermal comfort.